Association between frailty and dual sensory loss: hearing and vision - Garcia, Ana Carla Oliveira; Wittich, Walter; Momensohn-Santos, Teresa (Revista Kairós-Gerontologia, 2021)
Dual sensory loss (DSL) refers to the presence of both hearing- and vision- loss. The objective of this study was to explore the link between frailty and DSL in older adults. This cross-sectional study was conducted in a public health rehabilitation center with one hundred seven older adults Participants with hearing loss had significantly higher levels of frailty scores (p =0.014). We observed that the variable frailty had a statistically significant association with hearing loss, glaucoma, male older adults and cognitive decline a risk factor for frailty in older adults.